Beyond vernacular: Measurement solutions to the lexical fallacy in disgust research. (August 2021) - Armstrong, Thomas; Wilbanks, Danica; Leong, Daniel; Hsu, Kean
Highlights: Excessive disgust causes individual and societal problems and resists treatment. To make progress, disgust research may need improved measurement. Self-report measures are reliable, but may lack validity due to lay use of "disgust". Non-self-report measures are mostly unreliable and may lack validity. Provides recommendations for improving measurement quality. Abstract: Disgust may play an important role in several mental disorders, in part because disgust seems impervious to corrective information, a feature noted long before it was studied by clinical psychologists. A deeper understanding of disgust could improve not only the treatment of mental disorders, but also other societal problems involving this peculiar emotion. In this paper, we review the measurement of disgust and identify issues that hold back progress in understanding how to treat this emotion. First, self-report measures of disgust, although optimized in terms of reliability, are compromised in terms of validity due to the "lexical fallacy, " that is, the assumption that vernacular usage of emotion terms reveals natural kinds. Improved self-report measures that parse disgust from neighboring states of discomfort and disapproval can address this limitation, but these approaches are absent in clinical psychology. Second, "objective" measures of disgust, although free of vernacular limitations, require greater psychometric scrutiny. In a critical review, we find that most instrument-based measures fail to demonstrate adequate reliability, rendering them unsuitable for the individual differences research crucial to clinical psychology. In light of this assessment, we provide several recommendations for improving the reliability and validity of disgust measurement, including renewed attention to theory.